Pembinaan dan Pendampingan Internet Marketing Guna Peningkatan Daya Saing pada Usaha Mikro Handycraft di Kota Medan - Dedek Kurniawan Gultom; Delyana Rahmawany Pulungan; Salman Farisi (Jurnal Pemberdayaan Masyarakat, 2019)
The implementation of the Community Partnership Program (PKM) aims to provide guidance and assistance to partners of micro handicraft entrepreneurs in implementing and implementing internet marketing as a means of business promotion to improve competitiveness and be able to manage business management that has an impact on expanding market aspects. This PKM program is held in 12 (twelve) months. The stages in implementing this PKM begin with Preparation, Direct Practice, Self-training, Implementation, Evaluation, and Development. The approach method used is the Learning Needs Based Method, Learning Goals and Objective, and Participant Center. The results achieved at this PKM are that Partners already have an Online Shop Website, scientific publications in community service journals, Publications on mass media / online, increased understanding, and business management skills and internet marketing, increased competitiveness, increased science, and technology in society and improved governance community value in the form of peace.